Sosialisasi Perilaku Hidup Bersih dan Sehat Siswa Sekolah Dasar Desa Pasirtanjung, Kecamatan Tanjungsari, Kabupaten Bogor - Yudhaningrum, Lupi; Rosalinda, Irma; Widyastuti, Liza Yudhita; Fajar Rakhman, Gumgum Gumelar (Universitas Negeri Jakarta, 2023)
This paper is about the Psychology Universitas Negeri Jakarta Community Service team's activity in Tanjung Sari Village, Bogor Regency, West Java, as an effort to solve hygiene and environmental problems there. In this activity, children as the next generation were included as the target to apply clean and healthy behaviours for sustainable environmental hygiene. Activities were designated in interactive and exciting presentations, practices, games, and prizes for participants (elementary school students). As a result, there was enthusiasm for the activities and increased participants' understanding to apply in everyday life.